2019
DOI: 10.1002/jcp.28236
|View full text |Cite
|
Sign up to set email alerts
|

Zyxin as a potential cancer prognostic marker promotes the proliferation and metastasis of colorectal cancer cells

Abstract: Colorectal cancer (CRC) is a leading cause of cancer death. This study was conducted to investigate the functions and mechanisms of Zyxin (ZYX) in CRC. Multiomics analysis associated ZYX with CRC metastasis. ZYX expression levels were increased in human CRC tissues and related to shorter recurrence‐free survival. Knockdown of ZYX expression resulted in inhibition of cell growth, invasion, and migration in vitro and in vivo. Comprehensive analysis of gene microarray analysis showed that ZYX may activate the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
3
14
0
Order By: Relevance
“…6) [42][43][44][45][46][47][48] . This is in agreement with observations that zyxin influences cell migration, adhesion and proliferation as well as its potential involvement in cancer progression [49][50][51][52][53] . Zyxin's role in regulating cell survival is controversial [27][28][29][30] , but nuclear activities have generally been related to antiapoptotic effects 15,16 .…”
Section: Discussionsupporting
confidence: 92%
“…6) [42][43][44][45][46][47][48] . This is in agreement with observations that zyxin influences cell migration, adhesion and proliferation as well as its potential involvement in cancer progression [49][50][51][52][53] . Zyxin's role in regulating cell survival is controversial [27][28][29][30] , but nuclear activities have generally been related to antiapoptotic effects 15,16 .…”
Section: Discussionsupporting
confidence: 92%
“…In vitro experiments demonstrated that ZYX silencing in HCT116 colorectal cancer cell line caused decreased cell migration and invasion (58).…”
Section: Melanoma Elevated Levels Of Zyx Were Observed In Melanoma Cmentioning
confidence: 99%
“…Zhong et al showed that ZYX expression was significantly higher in colorectal cancer lesions in comparison to normal tissues (58). The patients with tumours characterised by high ZYX expression had a shorter recurrence-free survival (58).…”
Section: Melanoma Elevated Levels Of Zyx Were Observed In Melanoma Cmentioning
confidence: 99%
“…Strong focal adhesions (FA) are characteristic of the elongated mesenchymal invasive phenotype. Both N-glycosylation and zyxin upregulation (47,48) would suggest that YB-1 knock-out could also be prone to metastasize. Other strongly upregulated proteins included TGM2 which is a stress-responsive gene that encodes a multifunctional and structurally complex protein called tissue transglutaminase (TG2).…”
Section: Discussionmentioning
confidence: 99%